'Repackaging the emptiness': How Russian regional journalism adapts to the COVID-19 pandemic. (March 2023) - Erzikova, Elina; Lowrey, Wilson
The COVID-19 pandemic has underscored the role news organizations play in disseminating information and shaping public response to the crisis. This study adopts an ecological approach in examining Russian regional journalists' adaptations to the pandemic. Based on in-depth interviews, the study found that a worsened economic situation has increased dependence on state subsidies. Journalists avoided questioning authorities' response to COVID, with some publishing government information and others focusing on practical tips for readers.